'un día más de trabajo': Liberalisation Processes and the Precarity of Women in Roberto Bolaño's 2666. Issue 1 (14th May 2020) - Baker, Emily
This article explores the nexus between liberalisation processes, violence, gender, and ethics inRoberto Bolaño's final novel 2666 (2004 ). It does so first, with reference to a postcolonial framework, through the examination of a passage that juxtaposes different instances of gendered violence and precarity over time, associated with economic liberalisation; second, with reference to Slavoj Žižek's classifications of violence (also bound up with his critique of contemporary economic and political systems), it explores Bolaño's denunciation of the symbolic violence associated with the discursive construction of gender in Mexican society, which, in turn, reinforces systemic violence. Finally, I deployEmmanuel Levinas ' notion of the 'face' (in conjunction with Judith Butler's reading of it in Precarious Life ) to draw attention to the ethical imperative contained in the haunting of wealthy women by their murdered subaltern counterparts. I suggest that the presentation of the women in their tortured and murdered state strengthens the testimonial power of Bolaño's denunciation by disrupting the hegemonic landscape of representation which had previously succeeded in hiding them from view and silencing debates about the causes of their deaths. Tweetable abstract : Gender, liberalism, violence, and the ethics and politics of precarity inRoberto Bolaño's   2666